A national survey of Rett syndrome: Age, clinical characteristics, current abilities, and health. (28th March 2015) - Cianfaglione, Rina; Clarke, Angus; Kerr, Mike; Hastings, Richard P.; Oliver, Chris; Felce, David
<x xml:space="preserve">Abstract</x> As part of a wider study to investigate the behavioral phenotype of a national sample of girls and women with Rett syndrome (RTT) in comparison to a well‐chosen contrast group and its relationship to parental well‐being, the development, clinical severity, current abilities and health of 91 participants were analyzed in relation to diagnostic, clinical and genetic mutation categories. Early truncating mutations or large deletions were associated with greater severity. Early regression was also associated with greater severity. All three were associated with lower current abilities. Epilepsy and weight, gastrointestinal and bowel problems were common co‐morbidities. Participants with classic RTT had greater health problems than those with atypical RTT. A substantial minority of respondents reported fairly frequent signs of possible pain experienced by their relative with RTT. Overall, the study provides new data on the current abilities and general health of people with RTT and adds to the evidence that the severity of the condition and variation of subsequent disability, albeit generally within the profound range, may be related to gene mutation. The presence of certain co‐morbidities represents a substantial ongoing need for better health. The experience of pain requires further investigation. © 2015 Wiley Periodicals, Inc.